Analisis Fisiologis Kebugaran Jasmani Berdasarkan Kapasitas Aerobik (VO₂max) dan Tekanan Darah pada Siswa Sekolah Menengah Pertama - Fatoni Fatoni (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
Physical fitness is a crucial component of sports health and is closely related to an individual's physiological condition, particularly in adolescence. This study aims to analyze the fitness of students at Gowa State Junior High School 3 based on aerobic capacity (VO₂max) and blood pressure. The study used a quantitative approach with a descriptive correlational design. The study sample consisted of 58 students selected using a purposive sampling technique. Aerobic capacity was measured using the Multistage Fitness Test (MFT) to obtain an estimate of VO₂max, while blood pressure was measured at rest using a standard blood pressure monitor. Data were analyzed using SPSS version 25 through descriptive analysis and Pearson correlation test. The results showed that VO₂max had a positive and significant relationship with physical fitness (r = 0.62; p < 0.05), while systolic and diastolic blood pressure did not show a significant relationship with physical fitness (p > 0.05). These findings suggest that aerobic capacity is a more dominant physiological indicator in reflecting students' physical fitness than blood pressure. This study concludes that efforts to improve the fitness of junior high school students need to focus on developing physical activities that focus on increasing aerobic capacity in a structured and sustainable manner.